Digitalization and alternative marketing channels in the Uruguayan fruit and vegetable chain: Perspectives from main actors - Marcela Marques Berrutti; Jorge Álvarez; Federico García Suarez (Agrociencia Uruguay)
This study aims to delve into the potentials and difficulties of digitalization on the real commercial experience of some of the fundamental actors in the Uruguayan fruit and vegetable chain (producers, merchants, intermediaries, consumers, and private and public technicians). For that, these social actors and their projects were described and consulted in search of appreciations or points of view regarding technical innovations, barriers to commercialization, family labor, public policies, pressure for land use, and other complex problems. Through a “snowball sampling”, carrying out semi-structured questionnaires for more than 4 months from INIA Las Brujas, we obtained information mainly from actors in the south and some points in the northwest and east-central Uruguay. Opinions come from the complexity of people in their different roles, with the expected emergence of tensions and contradictions at different moments of the participatory-action research. We could appreciate that the Fourth and Fifth Industrial Revolution are having a significant impact in the Uruguayan fruit and vegetable chain. Digital technology is providing new tools for marketing such as: electronic commerce platforms, mobile applications, traceability and monitoring technologies for data analysis, etc. Support in this transformation comes both from private initiatives and public projects, some of which are outlined. We discuss some causes of digitalization disparities and some solutions, debating the role of each one of the represented actors and their possibilities of change.